The Effect of Addition of Cellulolytic Microbes from Rumen Fluid and Lactic Acid Bacteria in Pineapple Peel Fermentation on in vitro Digestibility - Hanim, Chusnul (2014)
The research was conducted to examine the effect of cellulolytic microbes from rumen fluid and lactic acid bacteria (LAB) addition into pineapple peel fermentation on in vitro digestibility. Cellulolytic microbes were added by 5% of dry matter (DM) into 300 g pineapple peel. Then, LAB was added after 4 d, 8 d, 12 d and 16 d of cellulolytic fermentation. Fermentation without addition of cellulolytic microbes and LAB was carried out as control. Fermentation was carried out in anaerobic condition at room temperature for 21 d with three replicates for each treatment. The fermented pineapple peel (FPP) was examined for physical quality including odor, color, texture, pH, the presence of fungi, as well as the lactic acid content. The FPP was also dried in 55°C, and then taken for chemical composition analysis including DM, organic matter (OM), crude fiber (CF), crude protein (CP), extract ether (EE) and nitrogen free extract (NFE) as well as in vitro digestibility including DM, OM and CF digestibility. The data obtained were analyzed using one way design and continued by Duncan’s new multiple range test to examine the differences among the mean values. The result showed that FPP had acid odor, brown colour, soft texture, and no fungi in all treatment. Addition of LAB on day 4th and 8th increased lactic acid content 2.4 times compare to control and CP (P<0.01), as well as decreased OM (P<0.01) and NFE (P<0.05). While addition of LAB on day 12th decreased CFD FPP by 26.44% compared to control and EE content (P<0.05). It could be concluded that addition of LAB at day 4 of pineapple peel fermentation with cellulolytic bacteria increased lactic acid content, but it did not have negative effect on in vitro digestibility. Key Words: Pineapple peel, Cellulolytic microbes, Lactic acid bacteria, Fermentation, In vitro digestibility